A global view of Pc3 wave activity in near-Earth space: Results from hybrid-Vlasov simulations - Turc, Lucile; Zhou, Hongyang; Tarvus, Vertti; Ala-Lahti, Matti; Battarbee, Markus; Pfau-Kempf, Yann; Johlander, Andreas; Ganse, Urs; Dubart, Maxime; George, Harriet; Grandin, Maxime; Horaites, Konstantinos; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Ultra-low frequency (ULF) waves in the Pc3 range, with periods between 10 – 45 s, are routinely observed in Earth’s dayside magnetosphere. They are thought to originate in the foreshock, which extends upstream of the quasi-parallel bow shock and is populated with shock-reflected particles. The foreshock is permeated with ULF waves generated by ion beam instabilities, most notably the ``30-second” waves whose periods match those of the Pc3 waves and which are carried earthward by the solar wind flow. However, the global picture of Pc3 wave activity from the foreshock to the magnetosphere and its response to changing solar wind conditions is still poorly understood. In this study, we investigate the global distribution and properties of Pc3 waves across near-Earth space using global simulations performed with the hybrid-Vlasov model Vlasiator. The simulations enable us to study the waves in their global context, and compare their properties in the foreshock, magnetosheath and dayside magnetosphere, for different sets of upstream solar wind conditions. We find that in all three regions the Pc3 wave power peaks at higher frequencies when the interplanetary magnetic field (IMF) strength is larger, consistent with previous studies. The Pc3 wave power is significantly enhanced in all three regions for higher solar wind Alfvén Mach number. As this parameter is known to affect the shock properties but has little impact inside the magnetosphere, this brings further support to the magnetospheric waves originating in the foreshock. Other parameters that are found to influence the foreshock wave power are the solar wind density and the IMF cone angle. Inside the magnetosphere, the wave power distribution depends strongly on the IMF orientation, which controls the foreshock position upstream of the bow shock. The wave power is largest when the angle between the IMF and the Sun-Earth line is smallest, suggesting that wave generation and transmission are most efficient in these conditions.